2020
DOI: 10.1016/j.ecss.2019.106512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tidal flooding on ecosystem CO2 and CH4 fluxes in a salt marsh in the Yellow River Delta

Abstract: Tidal flooding is the basic hydrological feature of a salt marsh, and controls its ecosystem carbon exchange. However, the response of ecosystem carbon exchange to different stages of tidal flooding remains poorly documented. To further explore this issue, we conducted a field experiment to assess the effect of tidal stages (before flooding stage, rising tide stage, tidal flooding stage and after ebbing stage), water levels (a control, a low water level (LWL), a middle water level (MWL) and a high water level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Carex lyngbyei were often found throughout both strata and so were not considered unique to one zone. The high marsh species' ranges align approximately with the mean extreme high-water line of estuarine marshes in Clayoquot Sound, while low marsh encompasses elevations between the mean lower high water and the mean extreme highwater lines (Jefferson, 1973, as cited in Deur, 2000Weinmann et al, 1984). This method was verified using detrended correspondence analysis, which showed that vegetation assemblages reflected distinct low and high marsh zones (Hill and Gauch, 1980;Appendix B).…”
Section: Field Samplingmentioning
confidence: 83%
See 1 more Smart Citation
“…Carex lyngbyei were often found throughout both strata and so were not considered unique to one zone. The high marsh species' ranges align approximately with the mean extreme high-water line of estuarine marshes in Clayoquot Sound, while low marsh encompasses elevations between the mean lower high water and the mean extreme highwater lines (Jefferson, 1973, as cited in Deur, 2000Weinmann et al, 1984). This method was verified using detrended correspondence analysis, which showed that vegetation assemblages reflected distinct low and high marsh zones (Hill and Gauch, 1980;Appendix B).…”
Section: Field Samplingmentioning
confidence: 83%
“…We note that, within this system, the partitioning between high and low marsh zones appears very closely linked with associated vegetation. Therefore, vegetation composition was recorded as an indicator of "low" vs. "high" marsh zones (Porter, 1982;Weinmann et al, 1984) around each coring spot. Coring spots were considered low marsh if the species Triglochin maritima, Salicornia spp., Fucus ssp., or Distichlis spicata were present and high marsh if it included Plantago maritima, Deschampsia caespitosa, Grindelia integrifolia, Potentilla anserina, Lysimachia maritima, or Eleocharis ssp.…”
Section: Field Samplingmentioning
confidence: 99%
“…The static chambers consisted of transparent acrylic plastic with three parts: a base frame (30 cm in diameter, 10, 10, 15, 20, 30, 40, 50 cm in height for the seven treatments, respectively), a removable middle box (30 cm in diameter, 100 cm in height) and a removable top box (30 cm in diameter, 100 cm in height). The base frames were installed into the soil to 5 cm depth, with 5 cm of the frame emerging above the water surface (Wei et al 2020), in the center of each plot in May 2018. The removable middle box was only used when the height of the vegetation was higher than 100 cm.…”
Section: Measurements Of Ecosystem Co 2 and Ch 4 Exchangementioning
confidence: 99%
“…S4b), inundation depth (0 cm) significantly increased soil CH 4 fluxes compared to the control due to anaerobic conditions which usually enhance CH 4 production by improving anaerobic decomposition by methanogenic bacteria and limiting CH 4 oxidation in reductive conditions (Kettunen et al 1999). Other studies showed that inundation could have little effect on CH 4 fluxes as the water column can provide a diffusion barrier to the release of CH 4 from the soil or water (Cheng et al 2007;Li et al 2018;Wei et al 2020). Moreover, growth of wetland plants (e.g.…”
Section: Effects Of Inundation Depth On Ecosystem Ch 4 Fluxesmentioning
confidence: 99%
“…On the one hand, when precipitation is low, coupled with increased air temperatures and evaporation rates, water-soluble salts from the sub-surface groundwater are transported upward through the root zone of plants to the soil surface from capillary rise (Yao and Yang 2010). Salinity stress tends to inhibit photosynthesis and productivity of marsh plants by influencing the leaf chlorophyll content, protein synthesis, and lipid metabolism of marsh plants (Abdul-Aziz et al, 2018, Wei et al, 2020b. Therefore, in many salt marshes, periodic inputs of freshwater from precipitation controls structure and function of their plant communities (Heinsch et al, 2004).…”
Section: Introductionmentioning
confidence: 99%